PARTISIPASI MASYARAKAT DALAM MELAKSANAKAN PROGRAM KELUARGA BERENCANA DI KECAMATAN MARGOYOSO KABUPATEN PATI - Muhadhofah Triana Husna; Moch. Mustam (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Family Planning aims to actualize quality family through promotion, protection, and assistance in establishing reproductive rights. Family Planning also provides services, regulation, and support to form families with ideal age of marriage, regulate the number, distance, and ideal age of children, regulate pregnancy, and foster family’s resilience and welfare. Problems in this research was the the increased number of population in Pati accompanied by the low level of community’s participation in Margoyoso among subdistricts in Pati. The purpose of this research was to know how the real portrait of the level of community’s participation in implementing Family Planning program. This research used quantitative approach with descriptive design. The results showed that the participation of PUS in Margoyoso was still low. Some elements of such participation include information, participation in consultation, participation in decision making, and participation in action. Some of younger PUS had low participation and some had high participation. On the other hand, older PUS mostly had low participation. PUS who had above-senior high school had higher participation than PUS who had under-school education, and PUS who had non-employment job had higher participation than PUS who had employment job. There are some strategies to increase the participation of PUS in implementing Family Planning program, such as increasing the role of Family Planning officer or government of each village to actively invite, support, motivate, and provide socialization, increasing the active participation of older PUS in family planning activities, increasing the role of PUS who have above-senior high school education, and increasing the role of PUS who have job as non-employee.